Beta Oscillations Distinguish Between Two Forms of Mental Imagery While Gamma and Theta Activity Reflects Auditory Attention - Villena-González, Mario; Palacios-García, Ismael; Rodríguez, Eugenio; López, Vladimir (Frontiers in Human Neuroscience, 2018)
Visual sensory processing of external events decreases when attention is internally oriented toward self-generated thoughts and also differences in attenuation have been shown depending on the thought’s modality (visual or auditory thought). The present study aims to assess whether such modulations occurs also in auditory modality. In order to investigate auditory sensory modulations, we compared a passive listening condition with two conditions in which attention was internally oriented as a part of a task; a visual imagery condition and an inner speech condition. EEG signal was recorded from 20 participants while they were exposed to auditory probes during these three conditions. ERP results showed no differences in N1 auditory response comparing the three conditions reflecting maintenance of evoked electrophysiological reactivity for auditory modality. Nonetheless, time-frequency analyses showed that gamma and theta power in frontal regions was higher for passive listening than for internal attentional conditions. Specifically, the reduced amplitude in early gamma and theta band during both inward attention conditions may reflect reduced conscious attention of the current auditory stimulation. Finally, different pattern of beta band activity was observed only during visual imagery which can reflect cross-modal integration between visual and auditory modalities and it can distinguish this form of mental imagery from the inner speech. Taken together, these results showed that attentional suppression mechanisms in auditory modality are different from visual modality during mental imagery processes. Our results about oscillatory activity also confirm the important role of gamma oscillations in auditory processing and the differential neural dynamics underlying the visual and auditory/verbal imagery.